Insecticide resistance of the field populations of oriental armyworm, Mythimna separata (Walker) in Shaanxi and Shanxi provinces of China - Yu-yu ZHAO; Li SU; Shuai LI; Yi-ping LI; Xiang-li XU; Wei-ning CHENG; Yi WANG; Jun-xiang WU (Journal of Integrative Agriculture, 2018)
Resistance of five field populations of Mythimna separata (Walker) collected from Shaanxi and Shanxi provinces of China to six different insecticides was evaluated by leaf dip method in the laboratory. The results showed that all populations were relatively sensitive to emamectin benzoate with a resistance ratio (RR) of 0.583–1.583 folds. All populations showed susceptible or low level resistance to chlorantraniliprole and beta-cypermethrin. Compared with a relatively susceptible strain of M. separata, the resistance level of the whole populations ranged from susceptible to moderate to chlorpyrifos and lambda-cyhalothrin, moderate to high to phoxim (RR=19.367–70.100) except for population from Sanyuan County (RR=2.567). Pair-wise correlation analysis among different insecticides indicated that chlorpyrifos has a significantly positive and significant correlation with emamectin benzoate. Chlorantraniliprole didn't have significant correlation with emamectin benzoate, chlorpyrifos and phoxim. Therefore, emamectin benzoate, chlorantraniliprole and beta-cypermethrin are recommended to control oriental armyworm. Meanwhile, to postpone the occurrence and development of insecticide resistance in Shaanxi and Shanxi provinces, alternative and rotational application of insecticides between chlorantraniliprole and emamectin benzoate or chlorpyrifos is necessary.